Journal of the Canadian Society for Syriac Studies (Gorgias Press, 2008)
The Canadian Society for Syriac Studies is a Toronto-based organization whose mission consists of promoting the study of the Syriac culture, a crossroad between the Sumerian, Babylonian, Assyrian, and Aramean civilizations and Eastern Christendom, and a link between the Semitic and Greek and Roman worlds. The CSSS focuses on Syriac literature, which is rooted in the same soil from which the ancient Mesopotamian and biblical literatures sprung; on Syriac art that bears Near Eastern characteristics as well as Byzantine influence; and on archaeology which unearths the history of the Syriac-speaking people: Assyrians, Chaldeans, Maronites and Catholic and Orthodox Syriacs. The CSSS is a not-for-profit organization, with no political or ideological affiliations or functions whatsoever. The Society's activities include the organization of a series of public lectures given by renowned scholars of Syriac studies worldwide, and one yearly symposium investigating individual topics of interest to Syriac. Other activities of the Society include showing films on Syriac antiquities and modern communities in their native contexts, exposing the public to the Syriac liturgical and hymnal music, and the organization of travels to Syriac sites. The CSSS was founded in 1999 at the University of Toronto, Department of Near and Middle Eastern Civilizations, as part of the latter's academic programme in Aramaic and Syriac languages and literatures. The CSSS was incorporated under the Canada Corporations Act in January 23, 1999.